Customer Satisfaction in the Era of Competition 5.0 - Andri Irawan; Dina Lusianti; Faridhatun Faidah (Institut Bisnis dan Teknologi Pelita Indonesia, 2023)
This study aims to examine the effect of store atmosphere, customer experience, facilities, and price on customer satisfaction at Papa Ron’s Pizza Kudus restaurant. This research uses quantitative research methods. Collecting data in this study using a questionnaire. The population in this study were customers of the Papa Ron’s Pizza Kudus restaurant. Sampling was carried out using a non-probability sampling technique with a total sample of 100 customers by taking the number of samples using the Lemeshow method. The test tool uses are the Statistical Program for Social Sciences (SPSS) Version 23. The results show that the store atmosphere, customer experience, facilities, and price variables simultaneously influence customer satisfaction. Furthermore, the store atmosphere variable has a positive and significant effect, then the customer experience variable has a positive and significant, the facilities variable has a positive and insignificant effect, then the price variable has a positive and significant effect on customer satisfaction.